(untitled) (International Journal of Statistical Sciences, 2026)
Understanding university students’ perceptions of women’s ideal age at first birth (WIAFB) is essential for informing future reproductive health policies and programs in a given country. This study aimed to survey Bangladeshi university students’ perspectives on WIAFB. A cross-sectional study was conducted at University of Rajshahi, Bangladesh and 466 unmarried students were recruited through multistage stratified random sampling. Students’ perspectives on WIAFB were measured using a question: “At what age do you think women should ideally have their first child?” Based on their responses, students were categorized into two groups: (i) early age at childbirth (<20 years), and (ii) ideal age at childbirth (20-30 years). In this study, 73.2% of university students preferred WIAFB between 20–30 years. A significantly higher proportion of female students (83.8%) reported a preference for WIAFB compared to males (66.3%). Students whose mothers had secondary or higher education were more likely to prefer WIAFB. Those with fathers who were farmers or businessmen held the same view. Financially stable students, and those not under family pressure were also more likely to prefer WIAFB. The study highlights that a majority of university students prefer WIAFB. Parental education, father’s occupation, financial stability, and the absence of family pressure were significantly associated with the preference. These insights underscore the need for targeted awareness programs for unmarried university students. Such initiatives should promote informed family planning decisions, encourage childbirth at an appropriate age, and help mitigate health risks associated with early pregnancies for both mothers and children. IJSS, Vol. 26(1), March, 2026, pp 135-146